Differences in Cholesterol Levels of Active Conventional Smokers and Active Electric Smokers Among Adolescents - Adriana, Adriana; Arwie, Dzikra; Novriani, Harmawati (CV. Science Tech Group, 2024)
Conventional cigarettes and electronic cigarettes (vapes) have become significant topics concerning their impact on health, including cholesterol levels. Nicotine in cigarettes can increase catecholamine secretion, triggering lipolysis and elevating cholesterol levels. High cholesterol levels may lead to atherosclerosis, posing a risk of coronary heart disease. Objective: This study aims to compare cholesterol levels between active conventional smokers and active electronic smokers among adolescents. Methods: This research utilized a laboratory observation design with a cross-sectional approach. The sample consisted of 30 adolescents, including 15 conventional smokers and 15 electronic smokers, selected using a purposive sampling technique. Results: Among conventional smokers, 13.3% had above-normal cholesterol levels, while this figure reached 40.0% for electronic smokers. The Mann-Whitney test revealed a p-value of 0.033 (p < 0.05), indicating a significant difference in cholesterol levels between the two groups. Conclusion: Electronic smokers exhibited higher cholesterol levels compared to conventional smokers. This finding suggests that electronic cigarette consumption poses a greater risk for elevated blood cholesterol levels.